Towards an establishment of a rating curve for suspended sediment transport by means of ADCP measurements - Rüther Nils; Aleixo Rui; Guerrero Massimo; Sørås Sigurd; Stokseth Siri (E3S Web of Conferences, 2018)
This study presents a series of acoustic current Doppler profiler (ADCP) measurements, which are converted into suspended load concentrations (SSC). Depending on the particle size distribution (PSD), the sound backscatter and its attenuation are used to determine a theoretical minimal and physical upper limit of the SSC. The SSC are displayed over time and compared with the evolution of the water level during the same time interval. The present study shows that it is possible to have continuous measurements of SSC and water level with a horizontally installed two beam equipped ADCP and discusses the potential of such a continuing times series measurement for application in hydraulic engineering and research. However, the presented data set shows also that the calibration and the filtering of the raw data has to be improved and that further investigations are needed. After data verification, it will be possible to calculate the yearly sediment load and investigate physical behaviour of SSC concentration as a function of water level and discharge.